Clinging to mammy : the faithful slave in twentieth-century America - McElya, Micki, 1972- (Harvard University Press, 2007)
Loving, hating, pitying, or pining for mammy became a way for Americans to make sense of shifting economic, social, and racial realities. Assertions of black contentment with servitude alleviated white fears while reinforcing racial hierarchy. McElya's stories expose the power and reach of this myth, not only in advertising, films, and literature about the South, but also in national monument proposals, child custody cases, New Negro activism, anti-lynching campaigns, and the civil rights movement.